The Effect Of Digital Bamboozle Game Toward Students’ Vocabulary Mastery (A Quasi Experimental Research on Eight Grade Students’ at SMP Negeri 14 Seluma Regency Academic Year 2024-2025) - Fitriani, Fitriani; Susanto, Ferri; Efrizal, Dedi (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
The study identified various problems encountered by teachers and students in the English learning process within the classroom, one of which being students' restricted vocabulary proficiency. One initiative to assist kids in memorizing vocabulary involves engaging methods, specifically the use of games. This study seeks to ascertain the substantial effect of the digital game Bamboozle on vocabulary acquisition among eighth-grade students at SMP Negeri 14 Seluma Regency. This research used quantitative method with quasi-experimental design. The population in this study were all eight grade students of SMP Negeri 14 Seluma Regency in the 2024-2025 school year. The sampling technique used was purposive sampling, with class VIII E as the experimental class and class VIII D as the control class. Data were collected through a multiple choice vocabulary test of 27 questions. The acquired data was analyzed using the t-test and f-test formulas. Researchers found that there was an increase in the post-test. The average value of the experimental class was 66.13 in the pretest and 86.53 in the posttest. The T-test result is higher than the t-table (7.419 > 1672) and the F-test is higher than the f table (55.039 > 4.00). Thus it can be concluded that there is a significant effect of using digital bamboozle game toward students’ vocabulary mastery on eight grade students’ at smp negeri 14 seluma regency academic year 2024-2025.